A multicentre, randomized, parallel group, superiority study to compare the clinical effectiveness and cost-effectiveness of external frame versus internal locking plate for complete articular pilon fracture fixation in adults: Protocol for the ACTIVE randomized controlled trial. (1st March 2021) - Flett, Lydia; Adamson, Joy; Barron, Elizabeth; Brealey, Stephen; Corbacho, Belen; Costa, Matthew L.; Gedney, Graham; Giotakis, Nikolaos; Hewitt, Catherine; Hugill-Jones, Jessica; Hukins, Deborah; Keding, Ada; et al.
Abstract : Aims: A pilon fracture is a severe ankle joint injury caused by high-energy trauma, typically affecting men of working age. Although relatively uncommon (5% to 7% of all tibial fractures), this injury causes among the worst functional and health outcomes of any skeletal injury, with a high risk of serious complications and long-term disability, and with devastating consequences on patients' quality of life and financial prospects. Robust evidence to guide treatment is currently lacking. This study aims to evaluate the clinical and cost-effectiveness of two surgical interventions that are most commonly used to treat pilon fractures. Methods: A randomized controlled trial (RCT) of 334 adult patients diagnosed with a closed type C pilon fracture will be conducted. Internal locking plate fixation will be compared with external frame fixation. The primary outcome and endpoint will be the Disability Rating Index (a patient self-reported assessment of physical disability) at 12 months. This will also be measured at baseline, three, six, and 24 months after randomization. Secondary outcomes include the Olerud and Molander Ankle Score (OMAS), the five-level EuroQol five-dimenison score (EQ-5D-5L), complications (including bone healing), resource use, work impact, and patient treatment preference. The acceptability of the treatments and study design to patients and health care professionals will be explored through qualitative methods. Discussion: The two treatments being compared are the most commonly used for this injury, however there is uncertainty over which is most clinically and cost-effective. The Articular Pilon Fracture (ACTIVE) Trial is a sufficiently powered and rigorously designed study to inform clinical decisions for the treatment of adults with this injury. Cite this article: Bone Jt Open 2021;2(3):150–163.